COVID-19- A Challenge for Urology Subspecialty in an overwhelmed public sector hospital: A Descriptive Review - Muhammad Asif, Shahzad-Ur-Rehman, Zakir Khan, Maryam Ikramullah, Syed Ikramullah, Romana Bibi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: COVID-19 has brought unprecedented changes in every aspect of life throughout the world including the healthcare delivery system. After a grinding halt in surgical practice due to this pandemic, the conventional protocols needed a thorough overhaul before kick-starting formal services. This study discusses ways and procedure changes adopted at the Urology department to navigate this crisis and extend adequate urological care to patients at the same time. Aim: To share our experience of patient management in the era of the COVID-19 pandemic. Methods: It’s a descriptive review article based on patient management protocols and clinical audit in the era of COVID-19 pandemic at the Departmentof Urology, MTI, Lady Reading Hospital from 20th Marchto 20th June 2020. Clinical implication the benefit of this study is how to organize things and continue health care provision in a deadly pandemic. Furthermore, it will set a precedence that how to cope with such a pandemic in the future. Conclusion: All surgical patients should be screened for COVID-19, with preference given to PCR tests. All elective surgeries should be put on hold as a result of the limited availability of ventilators, manpower, and hospital beds. Only semi-elective, lifesaving and oncologic surgeries that cannot be delayed should be done with full PPEs provided to every personnel frequenting operating theaters during the procedure. Furthermore, more efforts are needed to lift the infrastructure of hospitals and make them capable to face problems of such proportions in the future. Keywords: COVID-19, Urology, Public sector hospital, Pandemic, Oncological surgeries